Dhima za Kipragmatiki za Kialami Pragmatiki ‘ah’ katika Mazungumzo ya Kiswahili (JULACE: Journal of the University of Namibia Language Centre, 2018)
This study examines the pragmatic functions of the pragmatic markers ah in spoken Kiswahili. The data has been obtained from informal conversations made by Swahili speakers in informal social settings. These include ‘vijiwe vya kahawa’ (setting of informal conversations created around people drinking coffee) and ‘vijiwe vya mamantilie’ (setting of informal conversations around women preparing and selling food on the streets). Using Conversation Analysis (Sacks, 1962) and Contextualization Theory (Gumpers, 1982), the results show that the pragmatic marker ah conveys different meanings depending on context of use and hence has various pragmatic functions. Among the pragmatic functions identified in this article are; to be used as gap filler (the interlocutor is thinking about what to say), is used to start the conversation, is used to disagree with what the other interlocutor has said, to show that the speaker has changed from the state of not knowing to the state of knowing (Now I get you) and to show exclamation. Interestingly, also, the study shows that intonation and other paralinguistic features (like gestures) play a role in determining the pragmatic functions of this marker. Generally, this article concludes that pragmatic markers in spoken Kiswahili are rich in meanings. Therefore, they are wealthy to be investigated.
Keywords: pragmatic functions; pragmatic markers; iswahili language; Conversation Analysis; Contextualization Theory